Spectrum of Chronic Kidney Disease Without Hemodialysis - Elahi , Awais; Zaman, Haidar; Shah, Ahsen; Pervaiz, Jibran; Rabani, Bilal (Indus Journal of Bioscience Research, 2025)
Background: Chronic Kidney Disease is an irreversible process where the deterioration of the kidneys progresses, making it impossible to extract the wastes and fluid from the bloodstream, which further gives rise to various complications. The common factors promoting the advancement of CKD are diabetes mellitus, high blood pressure, and Hepatitis C infections. Effective management of comorbid conditions delays the progress of CKD. This research work focuses on the spectrum of CKD without hemodialysis and how comorbidities influence patients from the region of Abbottabad. Objective: To determine the frequency of spectrum of chronic kidney disease in patients without hemodialysis. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted from 26th March 2025 to 26th June 2025 at the Department of Nephrology, Ayub Teaching Hospital, Abbottabad. Methodology: Ninety patients aged 30 to 60 years, already diagnosed with CKD, were recruited. Information on demographics, comorbid conditions, and CKD stages was gathered. Diagnosis of diabetes involved fasting blood sugar and clinical history, and for hypertension, patients were confirmed if their BP was ≥ 140/90mmHg. Hepatitis C diagnosis involved the use of the PCR test. Analysis of the study was conducted using the IBM SPSS version 25 computer software program, and association was determined by the chi-squared test, where the significance level was p < 0.05. Results: The mean age of participants were 45.81 ± 9.03 years and the average BMI was 27.74 ± 2.71 kg/m². Diabetes mellitus was found in 32.2% patients, hypertension 31.1% and Hepatitis C virus was 15.6%. A significant association was observed between hypertension and female gender (p  0.011). The majority of patients were in Stage 3 of CKD (65.6%). Conclusion: Diabetes and hypertension are prevalent comorbidities among CKD patients, with hypertension showing a significant association with female gender.